Slackline training for Paralympic alpine sit skiers: Development of human‐device multi‐joint coordination - Liu, Kaiqi; Ji, Linhong; Capelli, Dario; Lu, Yijia (Scandinavian journal of medicine & science in sports, 2024)
Purpose Para‐alpine sit skiers face unique challenges in balance control due to their disabilities and the use of sit skis. This study assessed their multi‐joint coordination before and after slackline training. Methods Nine alpine sit skiers (6 M/3 F; 27 ± 8 years; height: 168.3 ± 6.0 cm; body mass: 55.4 ± 6.9 kg) with different disabilities (LW10‐LW12) volunteered for the experiment. All subjects performed slackline training for 5 weeks (20 sessions). Joint kinematics were captured by vision‐based markerless motion analysis. Root mean square (RMS) amplitude, mean velocity and mean power frequency (MPF) were evaluated. Results After training, performance improved significantly with an increase in balance time (1041%, p = 0.002), and a decrease in joint angular velocities and RMS amplitude of the sit ski foot (p < 0.05). Joint synergies were developed through in‐ or anti‐phase movements between joint pairs, particularly involving the hip joints (continuous relative phase angles ~0° or 180°, p < 0.001). Multi‐joint coordination shifted from large‐RMS amplitude of elbows to low‐MPF large‐RMS amplitude of the hip and shoulders (p < 0.05), with a significant increase of hip weighting (77.61%, p = 0.031) in the principal component analysis. The coordination was maintained with the change of slackline tension (p < 0.05). Athletes with severe trunk disabilities (LW10) had shorter balance time and poorer coordination than athletes with full trunk functions (LW12). Conclusions Our findings showed the development of joint coordination involving better control of the hip and sit skis during the challenging slackline training task.